The role of commercial diplomacy in promoting and facilitating international business - Agnieszka Hajdukiewicz (International Entrepreneurship Review, 2019)
Objective: The main aim of this paper is to examine the role and challenges of contemporary commercial diplomacy in business promotion and facilitation of international trade and investment.